2023
DOI: 10.3389/fnagi.2023.1213057
|View full text |Cite
|
Sign up to set email alerts
|

Myokines as mediators of exercise-induced cognitive changes in older adults: protocol for a comprehensive living systematic review and meta-analysis

Wouter A. J. Vints,
Evrim Gökçe,
Antoine Langeard
et al.

Abstract: BackgroundThe world’s population is aging, but life expectancy has risen more than healthy life expectancy (HALE). With respect to brain and cognition, the prevalence of neurodegenerative disorders increases with age, affecting health and quality of life, and imposing significant healthcare costs. Although the effects of physical exercise on cognition in advanced age have been widely explored, in-depth fundamental knowledge of the underlying mechanisms of the exercise-induced cognitive improvements is lacking.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 133 publications
0
4
0
Order By: Relevance
“…87 Several studies have found an association between BDNF and hippocampal neurogenesis leading to improved learning and memory. 86 In the context of CSVD, the Framingham Study found that higher BDNF was associated with less WMH volume over a median follow-up of 10 years. 88 Irisin is another hormone that is secreted from skeletal muscles during exercise.…”
Section: Exerkinesmentioning
confidence: 99%
See 3 more Smart Citations
“…87 Several studies have found an association between BDNF and hippocampal neurogenesis leading to improved learning and memory. 86 In the context of CSVD, the Framingham Study found that higher BDNF was associated with less WMH volume over a median follow-up of 10 years. 88 Irisin is another hormone that is secreted from skeletal muscles during exercise.…”
Section: Exerkinesmentioning
confidence: 99%
“…84 The skeletal muscle secretome consists of hundreds of myokines; relevant myokines for brain health include BDNF (brain-derived neurotrophic factor), irisin, cathepsin B, and IGF-1 (insulin-like growth factor 1). 86 BDNF plays an important role in neuronal growth, repair, and regeneration. 86 Following exercise, especially AT, BDNF levels increase in both the brain and skeletal muscle.…”
Section: Exerkinesmentioning
confidence: 99%
See 2 more Smart Citations